Asuhan Kebidanan Continuity of Care Ny. E Usia 27 Tahun G1P0A0 di RSIA Asih Balikpapan - Juwita Novita; Heni Hirawati Pranoto (Universitas Ngudi Waluyo, 2024)
Pregnancy, childbirth, postpartum, and neonates are physiological conditions that can potentially threaten the lives of mothers, babies and even cause death. One effort that can be made is to implement a comprehensive midwifery care model that can optimize the detection of high maternal neonatal risk. The purpose of the study was to analyze the implementation of midwifery care for pregnant women, giving birth, postpartum, BBL and KB. The research method was observational descriptive analytic. The case study approach to the implementation of midwifery care includes pregnancy, childbirth, newborns, postpartum, and family planning (KB) care. The sample was a pregnant woman G2 P1 A0 with a gestational age of 38 weeks. The research period was August 23-September 7, 2024 at RSIA Asih Balikpapan. The research instrument used the SOAP documentation method with a Varney management mindset. The collection technique used primary data through interviews, observations, physical examinations, and KIA books. The results of the care obtained were Mrs. E, a pregnant woman G2P1A0 with a gestational age of 38 weeks. The mother is pregnant with her second child with a gestational age of 9 months, the mother wants to check her pregnancy. The mother complained of tight stomach, frequent urination accompanied by blood and mucus, pain scale 8 (severe). On August 23 at 10.05 WITA to the Emergency Room at RSIA Asih Balikpapan because the stomach felt tight since 08.00 WITA and there was blood and mucus. To reduce the pain, endorphin massage was performed from 6 to 8 dilation. The baby was born spontaneously, immediately cried at 10.18 WITA, the placenta was born completely at 10.25 WITA and there was no bleeding. During the Postpartum Period Midwifery care during the postpartum period was carried out 3 times, namely, 6 hours postpartum, 7 days postpartum and 14 days postpartum. The results of subjective and objective data confirmed Mrs.